Deteksi Kebocoran Dan Sumbatan Pada Jaringan Pipa Mengunakan Sinyal Suara - Riedho Tilma Satria; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research describes the results obtained from experimental studies into the use of acoustic signals to detect leaks and blockages in pipelines. The piping system is an important feature in the industrial world, because it has an effective and efficient transportation function used for delivery such as drinking water, petrochemicals and other liquids. Prevention of damage to either leakage or blockage is very important because it can reduce the number of losses both the economy, the natural environment, even loss of life. The research method used is detection by using acoustic signal. Acoustic signal method is used because it is very sensitive to discontinuities in pipes that can detect problems quickly and precisely which has the advantage of cheaper cost. Acoustic signals are given for leakage, blockage, and joint damage to water and waterless conditions of different sizes and positions. The acoustic signal data is processed by fast Fourier transform and Wavelet Transform methods. From the test results obtained that the amount of damage given is directly proportional to the resulting amplitude. The conclusion is that this is an effective method for the detection of leaks and plugs in simple and enhanced pipes to monitor from more complex pipelines.Keywords : Sound Signal, Leakage, Blockage, Fast Fourier Transform, Wavelet Transform.